ASCENDING AORTA WALL DEFORMATION IN ESSENTIAL HYPERTENSIVE. A SPECKLE TRACKING IMAGING STUDY. (June 2018) - Marketou, M.; Patrianakos, A.; Maragkoudakis, S.; Vernardos, M.; Lempidakis, D.; Konstantinou, J.; Vougia, D.; Logakis, J.; Fragkiadakis, K.; Kochiadakis, G.; Parthenakis, F.
Abstract : Objective: Aortic stiffness plays has an important prognostic role in essential hypertension. Arterial wall tissues are sensitive to their mechanical surroundings and remodel their structure and mechanical properties when subjected to mechanical stimuli such as increased arterial pressure. The aim of this study is to determine the longitudinal strain (LS) of aortic wall using 2D -strain in hypertensive patients. Design and method: Forty five subjects, 24 without any sign of cardiovascular disease, (13 men, aged 52 ± 13years) and 21 patients with well controlled essential hypertension (12 men, aged 55 ± 15 years) were included in our study. All participants underwent a complete echocardiographic study and local aortic deformation was study as followed: Tracking of the anterior aortic wall from the left parasternal long axis view, started from the sinotubular junction and 3 cm thereafter and postprossecing analyzed with 2D-strain (Echopac v.11, GE). Aortic distensibility (AoD) was studied with the M-mode 3 cm after the sinotubular junction and was calculated as (End-systolic-End-diastolic) /end-systolic diameter *100. Results: There were no significant differences in mean age, blood pressure and ejection fraction between the two groups. Aortic wall tracking were feasible in 14 normal and 15 patients. Although there were no significance difference in AoD between the 2 groups (9.8 ± 1.8 % vs 6.7 ± 1.8 %, p = 0.08 in controls and hypertensives respectively) a significant difference was in aortic segmental (p < 0.01 for each segment) and averaged LS (averaged LS was −26.3 ± 6.9 % vs −20.4 ± 2.5 %, p = 0.007 in controls and pts respectively). A significant negative correlation between AoD and averaged aortic LS (r = −0.495, p = 0.01) was found. Conclusions: Our preliminary results suggest that essential hypertension is associated with a profound change in aortic wall mechanical properties. Speckle tracking promises new insights into aortic mechanics and can be evaluated in the daily clinical practice.